Individual Variability in von Willebrand Factor Fragility in Response to Shear Stress: A Possible Clue for Predicting Bleeding Risk. Issue 9 (28th December 2021) - Sakatsume, Ko; Akiyama, Masatoshi; Sakota, Daisuke; Hijikata, Wataru; Horiuchi, Hisanori; Maruyama, Osamu; Saiki, Yoshikatsu
Abstract : Acquired von Willebrand syndrome (AVWS), characterized by reduced von Willebrand factor (VWF) large multimers, has recently been implicated as the principal mechanism underlying bleeding in patients implanted with left ventricular assist devices (LVADs). Hematological severity of AVWS varies among patients, even if an identical device is implanted. We investigated whether this diversity in hematological severity is due to individual variability in VWF fragility, according to responses to incremental shear stress. Whole-blood samples were sheared at 20, 000–40, 000 s –1 shear rate, an index of shear stress, using a custom-made shear stressor that could generate shear stress compatible with that produced by an LVAD. The degree of VWF large multimers degradation was evaluated using the VWF large multimer index. A significant inverse correlation was observed between the VWF large multimer index and LVAD-compatible magnitudes of shear stress: the VWF large multimer indices were 68.5 ± 18.3, 48.0 ± 13.9, 33.9 ± 12.1, 23.7 ± 7.9, and 18.7% ± 8.7% at 20, 000, 25, 000, 30, 000, 35, 000, and 40, 000 s –1 of shear rates, respectively ( P < 0.0001). Furthermore, experimental VWF large multimer index values were compatible with those derived from patients with implanted LVADs (median; 28.9%). Finally, reduction in the VWF large multimer index corresponding to shear stress showed individual variation. We demonstrated that the combined use of a novel high shear stress loading device and quantitative evaluation of VWF large multimers may predict risk of bleeding before LVAD implantation.